Complex evaluation of efficiency of economical activities in construction enterprises/Statybos įmonių komercinės-ūkinės veiklos efektyvumo kompleksinis įvertinimas - Ginevičius, Romualdas; Podviezko, Valentinas (Journal of Civil Engineering and Management, 2000)
The means used at the present time for a complex evaluation of the efficiency of building enterprise activities are either oversimplified or too complicated. Therefore it is necessary to develop for practical needs convenient, simple and understandable means. The problem can be solved by methods based on a graphical-analytical interpretation. Among the comparatively simple means applied now for a complex evaluation are: by the sum of work places; evaluation based on a geometrical average; evaluation based on the sum of partial indices, etc. More complicated means include the multi-criteria complex proportional evaluation, etc. In case of the suggested graphical-analytical complex evaluation, different charts may be used, including pie charts. Three dimensions differ in them: partial indices, the corresponding central angles and the circle radius. There exist some cases of graphical-analytical evaluation. In the first case, the circle area in divided into n sectors, the area of each sector being equal to the value of a corresponding partial criterion. In the second case, the circle is also divided into n sectors. The radius of each sector equals the value of a corresponding partial index. The generalised index is equal to the sum of all sector areas, too. In the third case, the radii of all sectors are the same and their angles are proportional to the values of partial angles of each sector. After connecting by a line the points got in that way, a figure is obtained which describes the corresponding criterion. The sum of areas of all such figures reflects the value searched for. In all three cases the importance of partial indices can be estimated additionally. The calculations performed according to all existing and suggested cases have shown that the means for graphical-analytical complex evaluation are precise and can be applied in everyday activities. Article in Lithuanian. First Published Online: 26 Jul 2012